Ego depletion and its role regarding the attitudes and behavior toward sustainable food consumption - Daiss, Fabian; Siebertz, Markus; Jansen, Petra (Frontiers in Nutrition, 2025)
ObjectivesThe study’s main goal was to investigate the effect of ego depletion on explicit and implicit attitudes and behavior toward sustainable food consumption in the context of dual-process models describing sustainable behavior.Methods171 student participants completed an explicit rating and an affective priming task, respectively, at pre- and post-intervention, namely a six-minute transcription task to induce ego depletion. They then conducted a decision-making task (sustainable vs. less-sustainable chocolate bar) to test sustainable behavior during ego depletion.ResultsContrary to our hypotheses, explicit attitudes toward sustainable nutrition remained stable across conditions, showing no significant decline in the depletion group. Unexpectedly, implicit attitudes toward sustainable vegetarian nutrition became more negative over time, irrespective of the experimental condition. In the decision-making task, participants’ behavior was primarily predicted by their explicit attitudes post-intervention, rather than their implicit attitudes or ego depletion state.ConclusionThese findings challenge the assumption that ego depletion weakens explicit attitudes toward sustainable behavior, particularly vegetarian nutrition. Instead, explicit attitudes appear to be stable and the predominant predictor of sustainable food choices.